Expansion and Cell-Cycle Arrest: Common Denominators of Cellular Senescence. Issue 12 (December 2019) - Ogrodnik, Mikolaj; Salmonowicz, Hanna; Jurk, Diana; Passos, João F.
Abstract : Cellular senescence is a major driver of age-related diseases, and senotherapies are being tested in clinical trials. Despite its popularity, cellular senescence is weakly defined and is frequently referred to as irreversible cell-cycle arrest. In this article we hypothesize that cellular senescence is a phenotype that results from the coordination of two processes: cell expansion and cell-cycle arrest. We provide evidence for the compatibility of the proposed model with recent findings showing senescence in postmitotic tissues, wound healing, obesity, and development. We believe our model also explains why some characteristics of senescence can be found in non-senescent cells. Finally, we propose new avenues for research from our model. Highlights: Senescence markers are the result of cell-cycle arrest and expansion-stimulation signals. Senescent cells increase in vivo when cell-cycle arrest and expansion stimulation are present. Our model explains senescent markers in postmitotic and non-permanently arrested cells.